Assessment of the Effect of Covid-19 Pandemic Lockdown Dietary Diversity among Urban Households in Jos, Plateau State, Nigeria - Solomon Taiwo Folorunso; Ruth Alabi; Omolola Stephen-Adamu; Godfrey Onuwa (Turkish Journal of Agriculture: Food Science and Technology)
Dietary diversity became a global concern in improving health conditions through the habit of food group consumption by adding health dimension to the issue of food calorie consumption. Access to nutritionally adequate and good quality diet is essential to human health, productivity and work output. However, despite the various concerns by governments all over the world on ensuring that every household can at least provide three square meals per day, food insecurity continues to be a major development problem across the globe. This study assessed the effect of COVID-19 pandemic lockdown on households’ dietary diversity in Jos Metropolis, Plateau State, Nigeria. A multistage sampling technique was used to select 265 households. Data was collected using well-structured questionnaire. The analytical techniques were; Descriptive statistics, Dietary Diversity index and Z-Statistics Test. Gender, age, household size, education, marital status, cooperative membership and access to credit were the socioeconomic characteristics described. Result indicate that 86% of the households had low food dietary diversity while 14% of the households had high food dietary diversity before and after the pandemic lockdown. Similarly, 18% of the households had low calorie consumption while 82% of the households had high dietary diversity before and after the pandemic lockdown. Cereals, legumes/grains, oils/fat, roots and tubers, sugar and honey and meats were the most common food consumed by the households daily before and after the COVID-19 pandemic lockdown. Result further indicate that the pandemic lockdown had effect on the dietary diversity and food consumption patterns of the urban households. It can be concluded that the understanding of the effect of the COVID-19 pandemic lockdown on dietary diversity and food consumption patterns of households is important in developing policy measures such as social safety nets, home feeding programmes, the school feeding programme, conditional cash transfers schemes and improved marketing channels that will help mitigate against households falling into food insecurity during similar pandemic in the future.